Impact of attapulgite and basalt fiber additions on the performance of pumice-based foam concrete: mechanical, thermal, and durability properties - Bodur, Burak; Benli, Ahmet; Bayraktar, Oguzhan Yavuz; Alcan, Haluk Görkem; Kaplan, Gokhan; Aydın, Abdulkadir Cüneyt (Springer Science and Business Media LLC, 2025)
Abstract This study explored the combined effects of using attapulgite (ATP) as a partial cement replacement and basalt fibers (BF) as reinforcement in the development of high-performance foam concrete (FC) with 100% pumice aggregate. The experimental program included preparing FC mixtures with ATP replacements at 10%, 20%, and 30% by cement weight, and adding BF at volume fractions of 0.5%, 1.0%, and 2.0%. Key properties assessed were fresh flowability, compressive and flexural strengths, stress–strain behavior, thermal conductivity, and durability under sulfate exposure and high temperatures. Findings revealed a synergistic effect between ATP and BF, leading to significant performance enhancements across various parameters. The mixture with 30% ATP and 0.5% BF exhibited the highest compressive strength, reaching 19.45 MPa at 28 days and 22.11 MPa at 90 days, indicating improvements of 129.3% and 85.3% over the reference mix, respectively. This combination also achieved the lowest sorptivity, improved thermal stability, and better sulfate resistance, making it highly suitable for structural applications in harsh environments. In addition, the mixture with 10% ATP and 0.5% BF demonstrated the lowest thermal conductivity, reducing heat transfer by 4.2% compared to the control, which is beneficial for thermal insulation in building materials. Microstructural analysis using Scanning Electron Microscopy (SEM) showed that ATP’s pozzolanic reactivity led to a denser microstructure with stronger bonding, while BF effectively bridged micro-cracks, enhancing the FC matrix's durability. Overall, these results highlighted the potential of ATP and BF to significantly enhance FC’s mechanical, thermal, and durability properties, providing an eco-friendly solution with lower cement use and greater resilience to environmental stressors. This study contributes to sustainable construction technology by showcasing how ATP and BF can optimize FC performance, supporting its wider use in the construction industry.
Keywords: Pumice; Stress-Strain; Attapulgite; Strength; Durability; Basalt Fiber-Reinforced Foam Concrete